Organic / inorganic adhesive composition and gas barrier film containing same
Patent Information
- Application Number
- JP2023511849
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-19
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-08-19
AI Technical Summary
【0020】 一態様による有機·無機接着組成物は、無機物ガスバリア層、及びデバイスを構成する多様な有機物層との相互接着が可能であり、ガスバリア特性を向上させることができ、100℃以下の低温において、高速硬化が可能である。他の一態様によるガスバリアフィルムは、前記有機·無機接着組成物を含むことにより、向上されたガスバリア特性、及び高い透明性を有し、水蒸気透過率が低下されうる。
Smart Images

Figure 0007645363000005 
Figure 0007645363000006 
Figure 0007645363000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic / inorganic adhesive composition and a gas barrier film containing the same. [Background technology]
[0002] With the development of display technology, the need for gas barrier films is increasing. Since the gas barrier films are required to have high gas barrier properties, they mainly have a multilayer structure in which an organic layer and an inorganic layer are laminated on a flexible film substrate. In such a multilayer gas barrier film, the inorganic layer essentially plays a role of blocking gas, and the organic layer plays a role of flattening the lamination surface laminated on the inorganic layer, improving the adhesive strength between the substrate and the inorganic layer, and filling defects such as cracks and pinholes in the inorganic layer, thereby improving the gas barrier properties.
[0003] The gas barrier film of the multi-layer structure can obtain a desired level of gas barrier properties by adjusting the number of inorganic layers and organic layers. However, as the number of layers increases, the transparency decreases, and internal cracks may occur due to the difference in thermal expansion coefficient caused by the increase in thickness, which may result in a decrease in production yield and an increase in production costs.
[0004] Therefore, there remains a demand for a composition for forming a novel functional layer in a gas barrier film, and a gas barrier film containing the same. Summary of the Invention [Problem to be solved by the invention]
[0005] In one aspect, an organic-inorganic adhesive composition is provided that can be bonded to an inorganic gas barrier layer and various organic layers that constitute a device, can improve gas barrier properties, and can be rapidly cured at low temperatures of 100°C or less.
[0006] In another embodiment, a gas barrier film is provided that includes the organic / inorganic adhesive composition. [Means for solving the problem]
[0007] According to one aspect, An organic-inorganic adhesive composition, a silane compound having one or more functional groups selected from the group consisting of vinyl, acryloxy, methacryloxy, and combinations thereof; an amine group-containing compound; An isocyanate compound, an acid catalyst; The organic-inorganic adhesive composition has a pH of 5 to 8.
[0008] The amine group-containing compound can increase the pH of the organic-inorganic adhesive composition in the range of 2 to 6.
[0009] The organic / inorganic adhesive composition also exhibits a pH change of 0.5 or less over 48 hours.
[0010] The silane compound is C1-C 10 It also contains an alkoxysilane compound.
[0011] The organic-inorganic adhesive composition may further contain a silane compound having an epoxy group.
[0012] The weight ratio of the silane compound having an epoxy group to the silane compound having one or more functional groups selected from the group consisting of vinyl groups, acryloxy groups, methacryloxy groups, and combinations thereof is 1:1 to 1:100.
[0013] The content of the silane compound is 0.01 to 10 wt % based on the total weight of the organic-inorganic adhesive composition.
[0014] The organic / inorganic adhesive composition can be cured within 2 minutes at a temperature of 100° C. or less.
[0015] According to another aspect, A substrate; an inorganic gas barrier layer located on at least one surface of the substrate; A gas barrier film is provided, which includes an organic-inorganic adhesive layer, which is a cured layer derived from the organic-inorganic adhesive composition, on one side of the inorganic gas barrier layer.
[0016] The adhesive layer may further include an organic layer on one side of the organic-inorganic adhesive layer.
[0017] The organic / inorganic adhesive layer is capable of forming a radical bond with the organic layer.
[0018] The organic-inorganic adhesive layer has a thickness of 0.01 to 10 μm.
[0019] The gas barrier film may have a water vapor permeability reduced by 10% or more compared to a gas barrier film that does not include an organic / inorganic adhesive layer. Effect of the Invention
[0020] The organic-inorganic adhesive composition according to one embodiment can bond to an inorganic gas barrier layer and various organic layers constituting a device, can improve gas barrier properties, and can be rapidly cured at a low temperature of 100° C. or less. A gas barrier film according to another embodiment includes the organic-inorganic adhesive composition, and thus has improved gas barrier properties, high transparency, and reduced water vapor transmission rate. [Brief description of the drawings]
[0021] [Figure 1] 1 is a cross-sectional view of a gas barrier film according to an embodiment. [Diagram 2] FIG. 4 is a cross-sectional view of a gas barrier film according to another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, the organic / inorganic adhesive composition and the manufacturing method of the gas barrier film containing the same will be described in detail with reference to the examples and drawings of the present invention. Those examples are merely presented as examples to more specifically explain the present invention, and it will be obvious to those skilled in the art that the scope of the present invention is not limited by those examples.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. In case of conflict, the present specification, including definitions, will control. In addition, although methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention, suitable methods and materials are described herein.
[0024] In this specification, the term "comprise" means that it does not exclude other elements, but also includes other elements, unless specifically stated to the contrary.
[0025] As used herein, the term "and / or" is meant to include any and all combinations of the associated listed items. As used herein, the term "or" means "and / or." As used herein, the phrase "at least one" or "one or more" before an element may be used to refer to the entire list of elements, but not to the individual elements listed.
[0026] As used herein, the term "based photoinitiator" is meant to include any "photoinitiator or derivative thereof."
[0027] According to an embodiment, the organic-inorganic adhesive composition includes a silane compound having one or more functional groups selected from the group consisting of vinyl, acryloxy, methacryloxy, or a combination thereof, an amine group-containing compound, an isocyanate compound, and an acid catalyst, and the organic-inorganic adhesive composition has a pH of 5 to 8.
[0028] The organic-inorganic adhesive composition can adhere to an inorganic gas barrier layer and various organic layers constituting a device, improve gas barrier properties, and can be rapidly cured at a low temperature of 100°C or less.
[0029] The silane compound having one or more of the above-mentioned functional groups, such as vinyl, acryloxy, methacryloxy, or a combination thereof, contains a double bond and can form a radical bond with a radically polymerizable organic compound in another layer through UV curing, thereby interconnecting the organic layer and the inorganic gas barrier layer.
[0030] The silane compound is C1-C 10 It also contains an alkoxysilane compound.
[0031] Said C1-C 10 The alkoxysilane compound also contains an alkoxy group capable of forming a hydroxy group via hydrolysis. The hydroxy group formed via such hydrolysis can form a mutual chemical bond via a condensation reaction with the hydroxy group of the inorganic gas barrier layer.
[0032] For example, the silane compound having one or more vinyl, acryloxy, methacryloxy, or combinations thereof functional groups may include vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyl, 3-acryloxypropyltrimethoxysilane, or combinations thereof.
[0033] The silane compound having one or more functional groups selected from the group consisting of vinyl, acryloxy, methacryloxy, and combinations thereof may be in the form of a monomer, an oligomer, or a polymer.
[0034] The organic-inorganic adhesive composition may further contain a silane compound having an epoxy group. The epoxy group may be one or more.
[0035] The silane compound having an epoxy group can form a mutual chemical bond with the hydroxyl group of the inorganic gas barrier layer via an epoxy reaction.
[0036] The epoxy group may be a glycidyl group, a glycidoxy group, or an epoxidized C4-C 20 However, the present invention is not limited thereto, and may also include epoxy groups of various types, if desired.
[0037] For example, the silane compound having an epoxy group may include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, or a combination thereof.
[0038] C1-C having the epoxy group 10 The alkoxysilane compound may be in a monomeric form or in an oligomeric or polymeric form.
[0039] The weight ratio of the silane compound having an epoxy group to the silane compound having one or more functional groups of vinyl groups, acryloxy groups, methacryloxy groups, or a combination thereof may be 1:1 to 1:100, such as 1:1 to 1:80, such as 1:1 to 1:50, such as 1:1 to 1:30, or such as 1:1 to 1:10.
[0040] If the weight ratio of the silane compound having an epoxy group to the silane compound having one or more functional groups selected from the group consisting of vinyl groups, acryloxy groups, methacryloxy groups, and combinations thereof exceeds 1:100, the adhesive strength to the inorganic gas barrier layer due to the addition of the silane compound having an epoxy group will be reduced.
[0041] The content of the silane compound having one or more functional groups, such as vinyl groups, acryloxy groups, methacryloxy groups, or a combination thereof, based on the total weight of the organic-inorganic adhesive composition, may be 0.01 to 10 wt %, for example, 0.03 to 10 wt %, for example, 0.05 to 10 wt %, for example, 0.08 to 10 wt %, or for example, 1 to 10 wt %.
[0042] If the content of the silane compound having one or more of the functional groups of vinyl, acryloxy, methacryloxy, or a combination thereof is less than 0.01% by weight, the organic-inorganic adhesive layer is formed too thin, the adhesive strength between the organic layer and the inorganic gas barrier layer is reduced, and it becomes difficult to protect the inorganic gas barrier layer from the outside. In addition, defects such as cracks and pinholes in the inorganic gas barrier layer cannot be sufficiently filled, and the gas barrier properties are reduced.
[0043] If the content of the silane compound having one or more of the functional groups, such as vinyl groups, acryloxy groups, methacryloxy groups, or a combination thereof, exceeds 10% by weight, the organic-inorganic adhesive layer will be formed too thick, causing the gas barrier film to curl due to the difference in thermal expansion coefficient with the inorganic gas barrier layer or base film, and the thick adhesive layer will reduce the flexibility of the gas barrier film.
[0044] The amine group-containing compound may be in the form of a monomer having an amine group, or in the form of an oligomer or polymer.
[0045] The amine group-containing compound also includes an amine group-containing silane compound.
[0046] Examples of the amine group-containing compound include n-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, n-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, or combinations thereof.
[0047] The amine group-containing compound may also include isopropylamine, isobutylamine, isopentylamine, isoheptylamine, or combinations thereof.
[0048] The amine group-containing compound increases the pH of the organic-inorganic adhesive composition to a basic level, and can enhance the condensation reaction between the hydroxy group of the silane compound having one or more of the functional groups of vinyl groups, acryloxy groups, methacryloxy groups, or combinations thereof formed through hydrolysis, such as the hydroxy group of the alkoxysilane compound, and the condensation reaction between the silane compounds having one or more of the functional groups of vinyl groups, acryloxy groups, methacryloxy groups, or combinations thereof ....
[0049] The amine group-containing compound can increase the pH of the organic-inorganic adhesive composition in the range of 2 to 6. For example, the amine group-containing compound can increase the pH of the organic-inorganic adhesive composition in the range of 2 to 5.
[0050] If the pH range of the organic / inorganic adhesive composition exceeds 6, the amine group-containing compound undergoes a condensation reaction between the silane compound having one or more of the functional groups of vinyl, acryloxy, methacryloxy, or a combination thereof very quickly, and the solution undergoes a change over time in which the gelation of the silane compound having one or more of the functional groups of vinyl, acryloxy, methacryloxy, or a combination thereof progresses.
[0051] The isocyanate-based compound includes any of a monomolecule, oligomer, polymer, or derivative thereof having an isocyanate group.
[0052] For example, the isocyanate-based oligomer or polymer can react with the silane compound or amine group-containing compound having one or more of the functional groups of vinyl, acryloxy, methacryloxy, or a combination thereof to form a crosslinkable chemical bond. The crosslinkable chemical bond thus formed can further strengthen the bonding strength between the organic layer and the inorganic gas barrier layer.
[0053] The acid catalyst may be hydrochloric acid, nitric acid, sulfuric acid, formic acid, or acetic acid. However, the acid catalyst is not limited thereto, and may contain one or more of each of them. The acid catalyst may reduce the pH of the organic / inorganic adhesive composition with acidity, and promote the hydrolysis reaction of the alkoxy group of the silane compound having one or more of the functional groups of vinyl, acryloxy, methacryloxy, or a combination thereof, such as the alkoxy group of the alkoxysilane compound. The pH of the composition containing the silane compound having one or more of the functional groups of vinyl, acryloxy, methacryloxy, or a combination thereof and the acid catalyst may be 5 or less, or, for example, 4 or less.
[0054] The pH of the organic-inorganic adhesive composition may be from 5 to 8, or such as from 6 to 8.
[0055] If the pH of the organic-inorganic adhesive composition is less than 5, the condensation reaction between the hydroxyl group of the silane compound having one or more of the functional groups of vinyl group, acryloxy group, methacryloxy group, or a combination thereof, such as the alkoxysilane compound, and the hydroxyl group of the inorganic gas barrier layer is reduced, and the reaction time is prolonged or high reaction energy is required, resulting in an increase in the cost of the gas barrier film or a poor appearance of the gas barrier film, such as wrinkles caused by heat.
[0056] If the pH of the organic-inorganic adhesive composition exceeds 8, the condensation reaction between the hydroxyl group of the silane compound having one or more of the functional groups of vinyl groups, acryloxy groups, methacryloxy groups, or a combination thereof, such as the alkoxysilane compound, and the hydroxyl group of the inorganic gas barrier layer may be improved, but the condensation reaction between the silane compounds having one or more of the functional groups of vinyl groups, acryloxy groups, methacryloxy groups, or a combination thereof is also improved, causing a change over time in the solution in which the gelation of the silane compounds progresses.
[0057] The organic-inorganic adhesive composition has a pH change of 0.5 or less over 48 hours. For example, the organic-inorganic adhesive composition has a pH change of 0.4 or less, or, for example, 0.3 or less over 48 hours. This allows the reactivity of the silane compound having one or more functional groups of vinyl groups, acryloxy groups, methacryloxy groups, or combinations thereof in the organic-inorganic adhesive composition to be maintained constant.
[0058] The organic / inorganic adhesive composition may further contain a monomer, oligomer or polymer having a functional group such as a hydroxyl group, a carboxyl group, an amide group, a urea group or a thiol group, if necessary.
[0059] The organic-inorganic adhesive composition may also include one or more organic solvents, such as, but not limited to, alcohols, ketones, ethers, toluene, hexane, or benzene.
[0060] The organic / inorganic adhesive composition can be cured at a temperature of 100° C. or less within 2 minutes, for example, within 1 minute.
[0061] If the curing temperature of the organic-inorganic adhesive composition exceeds 100° C., the gas barrier film is subjected to a thermal shock, resulting in poor appearance such as heat-induced wrinkles. If the curing time of the organic-inorganic adhesive composition exceeds 2 minutes, the productivity of the gas barrier film is reduced, the price competitiveness is deteriorated, and the gas barrier film may also be subjected to a thermal shock.
[0062] Since the organic-inorganic adhesive composition requires low-temperature, high-speed curing, if necessary, a UV curing process can be added to evaporate the solvent of the organic-inorganic adhesive composition at a low temperature and then cure the composition through UV curing, thereby reducing the thermal shock applied to the gas barrier film.
[0063] The organic-inorganic adhesive composition may further include one or more radical bonding compounds and a photoinitiator.
[0064] Examples of the radical-binding compound include, but are not limited to, (meth)acrylates having one or more (meth)acryloyl groups in the molecule, (meth)acrylamide, maleimide, (meth)acrylic acid, maleic acid, itaconic acid, (meth)acrylaldehyde, (meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, and triallyl isocyanurate.
[0065] Examples of the photoinitiator include, but are not limited to, acetophenone-based photoinitiators, benzoin ether-based photoinitiators, benzophenone-based photoinitiators, and thioxanthone-based photoinitiators.
[0066] According to another embodiment, the gas barrier film includes a substrate, an inorganic gas barrier layer located on at least one side of the substrate, and an organic-inorganic adhesive layer, which is a cured layer derived from the organic-inorganic adhesive composition, on one side of the inorganic gas barrier layer.
[0067] FIG. 1 is a cross-sectional view of a gas barrier film 200 according to an embodiment.
[0068] Referring to FIG. 1, a gas barrier film 200 is formed by sequentially laminating a substrate 101, an inorganic gas barrier layer 102, and an organic-inorganic adhesive layer 110 which is a cured layer made from the organic-inorganic adhesive composition described above.
[0069] The gas barrier film 200 includes the organic-inorganic adhesive composition, and thus has improved gas barrier properties, high transparency, and reduced water vapor transmission rate.
[0070] The substrate 101 may be a transparent substrate, for example, a transparent flexible polymer substrate film. Examples of the transparent flexible polymer substrate film include polyethylene terephthalate, polyethylene naphthalate, polyarylate, polycarbonate, polyetherimide, polyamideimide, polyimide, polybenzoxazole, etc. However, the transparent flexible polymer substrate film is not limited thereto, and includes any transparent flexible polymer substrate film that can be used in the art. The substrate 101 may have a single layer structure or a multilayer structure of two or more layers.
[0071] The inorganic gas barrier layer 102 may be formed of a material selected from a metal, a metal oxide, a metal nitride, a metal carbide, or a combination thereof. The inorganic gas barrier layer 102 may be formed of, for example, one or more metals selected from Si, Al, Ti, Zr, and Ta, an oxide or nitride of the metal, or a combination thereof. The inorganic gas barrier layer 102 may be formed of, for example, silicon oxide or aluminum oxide, but is not limited thereto.
[0072] The inorganic gas barrier layer 102 may have a thickness of 5 to 200 nm, or for example, 5 to 100 nm. Within this thickness range, the inorganic gas barrier layer 102 may have improved optical properties, flexibility, and gas barrier properties.
[0073] The organic-inorganic adhesive layer 110 may have a thickness of 0.01 to 10 μm, for example, 0.05 to 10 μm, or for example, 0.05 to 5 μm.
[0074] If the thickness of the organic-inorganic adhesive layer 110 is less than 0.01 μm, the organic-inorganic adhesive strength will be insufficient, resulting in delamination in the organic layer or the inorganic gas barrier layer 102, and the organic-inorganic adhesive strength will not be able to fully compensate for defects such as cracks and pinholes in the inorganic gas barrier layer 102, resulting in reduced gas barrier properties.
[0075] If the thickness of the organic / inorganic adhesive layer 110 exceeds 10 μm, the difference in thermal expansion coefficient between the organic gas barrier layer 102 or the substrate 101 will cause the gas barrier film 200 to curl, and the thick adhesive layer will reduce the flexibility of the gas barrier film 200.
[0076] An organic layer may be further included on one side of the organic-inorganic adhesive layer 110. The organic layer may be, for example, a UV-curable acrylic coating layer. However, the organic layer is not limited thereto, and may be any coating layer containing an organic material that can be used in the art.
[0077] The organic-inorganic adhesive layer 110 contains a double bond and can form a radical bond with an organic layer.
[0078] The gas barrier film 200 may have a water vapor permeability reduced by 10% or more compared to a gas barrier film that does not include an organic / inorganic adhesive layer.
[0079] The water vapor permeability of the gas barrier film 200 on which the organic-inorganic adhesive layer 110 is laminated is, for example, 0.05 g / m 2 The organic-inorganic adhesive composition can fill defects such as pinholes or cracks in the inorganic gas barrier layer 102 to improve the gas barrier properties.
[0080] FIG. 2 is a cross-sectional view of a gas barrier film 300 according to another embodiment.
[0081] 2, the gas barrier film 300 includes a substrate 201, an inorganic gas barrier layer 202, a protective layer 203, and an organic-inorganic adhesive layer 210 laminated in this order. The protective layer 203 is a layer formed of an organic material or a mixture of an organic material and an inorganic material to protect the inorganic gas barrier layer 202 from the outside.
[0082] For example, the protective layer 203 may contain a silane compound. For example, the protective layer 203 may have a hydroxyl group on the surface due to an organic substance or a silane compound. The organic-inorganic adhesive layer 210 may chemically bond with the hydroxyl group of the protective layer 203, and may adhere to not only the inorganic gas barrier layer 202 but also the protective layer 203.
[0083] According to another embodiment, a method for producing a gas barrier film includes the steps of preparing a substrate, forming an inorganic gas barrier layer on at least one surface of the substrate, and printing or coating the organic-inorganic adhesive composition on one surface of the inorganic gas barrier layer to form an organic-inorganic adhesive layer. The method for producing a gas barrier film can provide a gas barrier film having improved gas barrier properties, high transparency, and reduced water vapor transmission rate.
[0084] The inorganic gas barrier layer may be formed by a sputtering method, an electron beam evaporation method, a chemical vapor deposition (CVD) method, a plasma enhanced chemical vapor deposition method, a plating method, etc. For example, the inorganic gas barrier layer may be formed by a sputtering method, an electron beam evaporation method, or a chemical vapor deposition (CVD) method.
[0085] The configuration and effects of the present invention will be described in more detail below through examples and comparative examples. However, these examples are provided to more specifically explain the present invention, and the scope of the present invention is not limited to these examples. EXAMPLES
[0086] Example 1: Gas barrier film production A polyethylene terephthalate (PET) film (PH8, thickness: 75 μm) was used as a transparent substrate. An aluminum oxide (Al2O3) film with a thickness of 30 nm was laminated on the upper surface of the polyethylene terephthalate film by chemical vapor deposition (CVD) to form an inorganic gas barrier layer.
[0087] Separately, an organic / inorganic adhesive composition was prepared in the following manner. 15g of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical (KBM-503)) was added to a mixed solvent of 51g of isopropyl alcohol (IPA) and 17g of deionized water (Daejung Chemicals & Metals). Then, the 3-methacryloxypropyltrimethoxysilane-containing solution was adjusted to pH 3.0 using hydrochloric acid as an acid catalyst with a pH meter (Thermo Scientific (Orion 3-Star)) and stirred at 150 rpm for 1 hour to produce a primary mixture. Then, 267g of isopropyl alcohol and 5g of deionized water were mixed with the primary mixture, and 225g of a diluted solution of polyisocyanate (Samwon (CAT-45)) diluted in isopropyl alcohol solvent at a weight ratio of 1:5 was added and stirred at 150 rpm for 10 minutes to produce a secondary mixture. Thereafter, 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was added to the secondary mixture so that the pH of the solution was adjusted to 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), and the mixture was stirred at 150 rpm for 10 minutes to produce an organic-inorganic adhesive composition.
[0088] The organic-inorganic adhesive composition was bar-coated on the upper surface of the inorganic gas barrier layer and then rapidly cured at a temperature of 100°C for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm, thereby producing a gas barrier film.
[0089] Example 2: Gas barrier film production A gas barrier film was manufactured in the same manner as in Example 1, except that the pH of the second mixture was adjusted to 5.5 instead of 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was added, and the mixture was stirred at 150 rpm for 10 minutes to manufacture an organic-inorganic adhesive composition.
[0090] Example 3: Gas barrier film production A gas barrier film was manufactured in the same manner as in Example 1, except that isopentylamine (Sigma-Aldrich) was used instead of 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) to adjust the pH of the second mixture to 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)).
[0091] Example 4: Gas barrier film production A gas barrier film was manufactured in the same manner as in Example 1, except that 15 g of a silane oligomer having an acryloxy group and a methacryloxy group (Shin-Etsu Chemical Co., Ltd. (KR-513)) was added to a solvent prepared by mixing 51 g of isopropyl alcohol (IPA) and 17 g of deionized water (Daejung Chemicals & Metals), instead of adding 15 g of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-503)).
[0092] Example 5: Gas barrier film production A gas barrier film was manufactured in the same manner as in Example 1, except that, instead of adding 15 g of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-403) to a solvent mixture of 51 g of isopropyl alcohol (IPA) and 17 g of deionized water (Daejung Chemicals & Metals), 15 g of a mixture of 3-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-403) and 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-503) in a weight ratio of 1:3 was added, and hydrochloric acid was used as an acid catalyst for the mixture containing 3-glycidoxypropyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane.
[0093] Example 6: Gas barrier film production The organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer. The organic-inorganic adhesive composition was rapidly cured at 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm. The same method as in Example 1 was carried out to prepare a gas barrier film, except that the organic-inorganic adhesive composition was left at room temperature for 48 hours, bar-coated on the inorganic gas barrier layer, and rapidly cured at 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm.
[0094] Example 7: Gas barrier film production The pH of the second mixture was adjusted to 5.5 instead of 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical (KBM-903)) was added, and the mixture was stirred at 150 rpm for 10 minutes to prepare an organic-inorganic adhesive composition. The organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm. The same method as in Example 1 was carried out to prepare a gas barrier film, except that the organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm.
[0095] Example 8: Gas barrier film production 51 g of isopropyl alcohol (IPA) and deionized water (Daejung Chemicals & Instead of adding 15 g of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-503) to a solvent containing 17 g of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-403) and 15 g of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-503) in a weight ratio of 1:3, 15 g of a mixture was added, and hydrochloric acid was used as an acid catalyst for the mixture containing 3-glycidoxypropyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane to prepare an organic-inorganic adhesive composition. The organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer, and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm. The same method as in Example 1 was carried out, except that a gas barrier film was prepared.
[0096] Comparative Example 1: Gas Barrier Film Production A gas barrier film was produced in the same manner as in Example 1, except that no organic-inorganic adhesive layer was formed on the inorganic gas barrier layer.
[0097] Comparative Example 2: Gas Barrier Film Production A gas barrier film was manufactured in the same manner as in Example 1, except that an organic / inorganic adhesive composition without 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was used.
[0098] Comparative Example 3: Gas Barrier Film Production The 3-methacryloxypropyltrimethoxysilane-containing solution was treated with hydrochloric acid as an acid catalyst, and the pH of the solution was adjusted to 5.0 instead of 3.0 using a pH meter (Thermo Scientific (Orion 3-Star)). The solution was stirred at 150 rpm for 1 hour to prepare a first mixture. A gas barrier film was prepared in the same manner as in Example 1, except that 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical (KBM-903)) was not added to the second mixture.
[0099] Comparative Example 4: Gas Barrier Film Production A gas barrier film was manufactured in the same manner as in Example 1, except that 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was added to the second mixture so that the pH of the solution was adjusted to 4.5 instead of 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), and the mixture was stirred at 150 rpm for 10 minutes to manufacture an organic-inorganic adhesive composition.
[0100] Comparative Example 5: Gas Barrier Film Production A gas barrier film was manufactured in the same manner as in Example 1, except that 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was added to the second mixture so that the pH of the solution was adjusted to 9.5 instead of 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), and the mixture was stirred at 150 rpm for 10 minutes to manufacture an organic-inorganic adhesive composition.
[0101] Comparative Example 6: Gas Barrier Film Production The 3-methacryloxypropyltrimethoxysilane-containing solution was used as an acid catalyst, and the pH of the solution was adjusted to 5.0 instead of 3.0 using a pH meter (Thermo Scientific (Orion 3-Star)). The solution was stirred at 150 rpm for 1 hour to prepare a first mixture. An organic-inorganic adhesive composition was prepared from the second mixture without adding 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)). The organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer. The organic-inorganic adhesive composition was rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm. The same method as in Example 1 was carried out to prepare a gas barrier film.
[0102] Comparative Example 7: Gas Barrier Film Production 3-Aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was added to the secondary mixture so that the pH of the solution was 4.5 instead of 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), and the mixture was stirred at 150 rpm for 10 minutes to prepare an organic-inorganic adhesive composition. The organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm. A gas barrier film was prepared by carrying out the same method as in Example 1, except that the organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm.
[0103] Comparative Example 8: Gas Barrier Film Production 3-Aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. (KBM-903)) was added to the secondary mixture so that the pH of the solution was 9.5 instead of 8.0 using a pH meter (Thermo Scientific (Orion 3-Star)), and the mixture was stirred at 150 rpm for 10 minutes to prepare an organic-inorganic adhesive composition. The organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm. A gas barrier film was prepared by carrying out the same method as in Example 1, except that the organic-inorganic adhesive composition was left at room temperature for 48 hours, and then bar-coated on the inorganic gas barrier layer and rapidly cured at a temperature of 100° C. for 1 minute to form an organic-inorganic adhesive layer having a thickness of 0.3 μm.
[0104] Evaluation example 1: Physical property evaluation The physical properties of the gas barrier films produced in Examples 1 to 8 and Comparative Examples 1 to 8 were evaluated by the following methods.
[0105] (1)pH measurement The initial (0 hr) pH of the organic-inorganic adhesive composition used in Examples 1 to 5 and the pH after leaving the organic-inorganic composition at room temperature for 48 hours (48 hr) were measured using a pH meter (Thermo Scientific (Orion 3-Star)) and are shown in Table 1 below.
[0106] (2) Measurement of adhesion between organic / inorganic adhesive layer and inorganic gas barrier layer The adhesive strength between the organic / inorganic adhesive layer and the inorganic gas barrier layer of the gas barrier film manufactured by Examples 1 to 8, Comparative Examples 2 to 4, and Comparative Examples 6 to 8 was measured at room temperature and at high temperature and high humidity (60°C, 90% relative humidity, 96 hours). The adhesive strength between the organic / inorganic adhesive layer and the inorganic gas barrier layer was measured in % based on the total area to which the tape was attached when the surface of the organic / inorganic adhesive layer was cut into an X shape, tape was attached, and then the tape was peeled off vertically according to ASTM D3359-02. The adhesive strength was expressed in the form of 5B (peeled area 0%), 4B (peeled area less than 5%), 3B (peeled area less than 15%), 2B (peeled area less than 35%), 1B (peeled area less than 65%), and 0B (peeled area 65% or more), and shown in Table 2 below.
[0107] (3) Measurement of adhesion between organic / inorganic adhesive layers or inorganic gas barrier layers and organic layers The adhesive strength between the organic layer and the organic-inorganic adhesive layer of the gas barrier film produced in Examples 1 to 8, or the inorganic gas barrier layer of the gas barrier film produced in Comparative Example 1, was measured. The organic layer was prepared by bar-coating a UV-curable acrylic solution (JSR (OPSTAR Z7535)) on the upper surface of the organic-inorganic adhesive layer (Examples 1 to 8) or the inorganic gas barrier layer (Comparative Example 1) of the gas barrier film, and applying 200 mJ / cm 2 The adhesive strength was measured at room temperature and at high temperature and humidity (60°C, 90% relative humidity, 96 hours) in the same manner as in "(2) Measurement of adhesive strength between organic / inorganic adhesive layer and inorganic gas barrier layer" above, and shown in Table 3 below.
[0108] (4) Measurement of water vapor transmission rate The water vapor transmission rate (WVTR) of the gas barrier films prepared in Examples 1 to 8 and Comparative Example 1 was measured. The water vapor transmission rate was measured in the film thickness direction under conditions of 38° C. and 100% relative humidity using equipment from MOCON.
[0109] [Table 1]
[0110] As can be seen from Table 1, the organic-inorganic adhesive compositions used in Examples 1 to 5 had a pH change of 0.5 or less even after 48 hours, and the solution showed little change over time.
[0111] [Table 2]
[0112] As can be seen from Table 2, the adhesive strength between the organic / inorganic adhesive layer and the inorganic gas barrier layer of the gas barrier films produced in Examples 1 to 8 at room temperature and at high temperature and humidity (60°C, 90% relative humidity, 96 hours) was improved to 5B.
[0113] In comparison, the adhesive strength between the organic / inorganic adhesive layer and the inorganic gas barrier layer of the gas barrier films produced in Comparative Examples 2 to 4 and Comparative Examples 6 to 8 at room temperature and at high temperature and humidity (60°C, 90% relative humidity, 96 hours) was low, at 2B or less.
[0114] [Table 3]
[0115] As can be seen from Table 3, the adhesive strength between the organic / inorganic adhesive layer and the organic layer of the gas barrier films produced in Examples 1 to 8 was improved to 5B.
[0116] In comparison, it can be seen that the adhesive strength between the inorganic gas barrier layer and the organic layer of the gas barrier film produced in Comparative Example 1 is very low, at 0B.
[0117] [Table 4]
[0118] As can be seen from Table 4, the water vapor permeability of the gas barrier films prepared in Examples 1 to 8 was confirmed to be lower than 37.5% compared to the gas barrier film prepared in Comparative Example 1, which did not include an organic / inorganic adhesive layer.
[0119] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the claims also belong to the scope of the present invention.
Claims
1. An organic-inorganic adhesive composition, a silane compound having one or more functional groups selected from the group consisting of vinyl groups, acryloxy groups, methacryloxy groups, and combinations thereof; a silane compound having an epoxy group; an amine group-containing compound; An isocyanate compound, Including, The content of the silane compound having one or more functional groups selected from the group consisting of vinyl, acryloxy, methacryloxy, and combinations thereof is 0.01 to 10 wt % based on the total weight of the organic-inorganic adhesive composition; The organic-inorganic adhesive composition has a pH of 5 to 8; The organic-inorganic adhesive composition, wherein the weight ratio of the silane compound having an epoxy group to the silane compound having one or more functional groups selected from the group consisting of vinyl groups, acryloxy groups, methacryloxy groups, and combinations thereof is 1:1 to 1:
100.
2. The organic-inorganic adhesive composition according to claim 1 , wherein the pH of the organic-inorganic adhesive composition is adjusted by the content of the amine group-containing compound.
3. The organic-inorganic adhesive composition according to claim 1 , wherein the organic-inorganic adhesive composition exhibits a pH change of 0.5 or less over 48 hours.
4. The silane compound having one or more functional groups, such as vinyl groups, acryloxy groups, methacryloxy groups, or combinations thereof, is 1 -C 10 The organic-inorganic adhesive composition according to claim 1 , further comprising an alkoxysilyl group.
5. The organic-inorganic adhesive composition according to claim 1 , which is capable of curing within 2 minutes at a temperature of 100° C. or less.
6. A substrate; an inorganic gas barrier layer located on at least one surface of the substrate; A gas barrier film comprising: an organic-inorganic adhesive layer, which is a cured layer derived from the organic-inorganic adhesive composition according to claim 1 , on one side of the inorganic gas barrier layer.
7. The gas barrier film according to claim 6 , further comprising an organic layer on one side of the organic-inorganic adhesive layer.
8. The gas barrier film according to claim 7 , wherein the organic-inorganic adhesive layer is capable of forming a radical bond with the organic layer.
9. 7. The gas barrier film according to claim 6, wherein the organic-inorganic adhesive layer has a thickness of 0.01 to 10 [mu]m.
10. The gas barrier film according to claim 6 , wherein the water vapor transmission rate of the gas barrier film is reduced by 10% or more compared to a gas barrier film not including the organic-inorganic adhesive layer.
Citation Information
Patent Citations
Coating composition
JP1988048363A
Hydrophobic metal oxide powder and electrophotographic developer containing the same
JP1996152736A
Production of granular organopolysiloxane
JP1999130861A
Adhesive for inorganic vapor-deposited film
JP2002275448A
Urethane resin-based contact-type adhesive
JP2003027032A